Voices of D-Day the story of the Allied invasion told by those who were there (Eisenhower Center studies on war and peace, 1994)
Since 1983, the Eisenhower Center at the University of New Orleans has been engaged in a project to collect on audiotape and videotape the recollections of as many people as possible - soldiers as well as civilians - who were involved in one of the most historic events of the century - the June 6, 1944, Allied invasion of Normandy and Hitler's Fortress Europe